Answer:
-4 and -7
Explanation:
Given two equations
1. -2x - 2y = 22
2. x = -3y - 25
Substitute -3y - 25 for x in equation 1.
We have
-2x - 2y = 22
-2(-3y - 25) - 2y = 22
Expand the bracket
-2 X -3y + 2 x 25 - 2y = 22
6y + 50 - 2y = 22
6y - 2y + 50 = 22
4y + 50 = 22
Subtract 50 from both sides to eliminate 50 on the left side
4y + 50 - 50 = 22 - 50
4y = -28
Divide both sides by -8 to isolate y
4y/4 = -28/4
y = -7
Now substitute -7 for y in equation two to get x
We have
x =-3y - 25
= -3(-7) - 25
= -3 x -7 - 25
= 21 - 25
= -4
x = -4
x = -4
y = -7
Check
-2x - 2y = 22
-2(-4) -2(-7) = 22
8 + 14 = 22
22 = 22